Visualization of fibroblast activation after myocardial infarction using 68Ga-FAPI-PET. (14th October 2021) - Kupusovic, J; Kessler, L; Ferdinandus, J; Hirmas, N; Fendler, W; Totzeck, M; Herrmann, K; Wakili, R; Rischpler, C; Rassaf, T; Siebermair, J
Abstract: Introduction: Fibroblast activation protein (FAP) alpha specifically expressed by activated fibroblasts has been shown to be significantly involved in processes of tissue healing after injury, including fibrotic remodeling after myocardial infarction (MI). Positron-emission tomography (PET) with the tracer FAP-inhibitor (FAPI) is a novel diagnostic tool primarily described in oncologic patients for tumor stroma detection. We present data from a pilot study investigating patients after MI who underwent subsequent 68Ga-FAPI-PET for assessment of potential FAP-related myocardial remodeling. Methods: In this retrospective study we analyzed a cohort of 10 post-MI patients who underwent 68Ga-FAPI-PET imaging with respect to cardiac tracer pattern. Standardized maximum and mean uptake values and total volume of tracer enrichment (fibroblast activation volume, FAV) of the infarcted area were calculated. A visual grading scale was established to assess the level of agreement between maximum localized tracer uptake and segments belonging to the supply area of the culprit vessel. Tracer uptake was correlated to clinical variables, with readers blinded to the clinical characteristics. Results: Focal 68Ga-FAPI uptake was detected in all 10/10 patients after MI. According to our grading system for visual agreement of polar map segments and culprit lesion, we observed a very good (in 37.5% of patients) and a moderate (62.5% of patients) match between tracer uptake and the culprit lesion, respectively. We demonstrated a negative correlation of FAV uptake and left ventricular systolic function (R 2 =−0.69, p<0.05) and a very strong positive correlation of FAV and peak creatinine kinase level (R 2 =0.90, p<0.01). Conclusion: Increased myocardial 68Ga-FAPI uptake, serving as a surrogate for FAP expression after MI, corresponds well to the supply area of the culprit coronary vessel as well as to biomarker levels of myocardial injury. This imaging technique represents a highly promising, novel bio-signal in the assessment of myocardial injury and consecutive remodeling. Large controlled studies are warranted to further evaluate the prognostic impact of this novel imaging technique. Funding Acknowledgement: Type of funding sources: None.